Federalism: The idea from a philosophical perspective and solutions to legislative problems - Saad, George; Bahari, Karwan Ezzat Bari (Journal of Legal and Political Studies, 2025)
The idea of federalism is the highest point that political genius has reached to this day. It is the problem of reconciling freedom and authority. In the first section, we discuss the Proudhonian position on liberal federalism, which is completely different from the federalism we know in America, Switzerland, or even Iraqi Kurdistan. In Proudhon's view, "Whoever lays his hand on me to rule me is a usurper and a tyrant. I declare him my enemy." This idea of Proudhonian federalism establishes true independence for collective beings, from individuals to all of humanity, passing through all the different intermediate geographical levels. In the Proudhonian approach, federalism is the decision from the bottom up, and there is no central authority except at the minimum and for organizational matters. We also discuss the close relationship between federalism in the Proudhonian sense and the concept of self-management. Self-management focuses on the role of general assemblies, voting, and the minority's submission to the opinion of the majority. Then we raise problems related to federalism in the traditional sense and ask to what extent this federalism can be achieved in the European Union. We devote space to the role of constitutional courts (especially the US Supreme Court and its important role since the Marbury v. Madison decision (. Finally, in the second section, we devote space to the situation in Iraqi Kurdistan and present two opinions: the first opinion that is never satisfied with the reality of things because Baghdad still holds the reins of decision-making, and the other opinion that sees in the articles of the Iraqi constitution and the contradiction that characterizes some of its articles an enormous power granted to Kurdistan. Finally, we say, for the sake of an amusing comparison, what would Proudhon have done if he had been a federal Kurd living in Dohuk. Keywords: Federalism, Joseph Proudhon, Self-Administration, Iraqi Constitution, Iraqi Kurdistan, Anarchist Thought.
Keywords: Federalism; Joseph Proudhon; SelfAdministration; Iraqi Constitution; Iraqi Kurdistan; Anarchist Thought